An Analysis of Eleventh-Grade Students’ Grammatical Mistakes in Using Present Perfect Tense through Communicative Test at SMAN 1 Batipuh - Kurnia Fitri; Muhd. Al Hafizh (Journal of English Language Teaching, 2022)
This study was aiming at finding out the most mistakes in using present perfect tense and knowing the causes why the students at SMAN 1 Batipuh made mistakes in using present perfect tense. The students grade XI from social class were the population of this study and the samples of were 58 students taken from IPS 2 and IPS 3 classes at SMAN 1 Batipuh. The cluster random sampling technique was used to determine the samples. The mixed method research was used in this study. Then, test and interview guide were used to collect the data of this study. Finally, the findings showed that omission, addition, misformation, and misordering were the four types of mistakes made by the students. From the frequency of each mistake, misformation was the most frequently mistakes produced by the students. It took 51.61% of the total mistakes. Moreover, 24.19% of mistakes fell into omission and 14.51% of mistakes fell into addition; whereas misordering took 9.67%. From the result of interview, these mistakes were conducted because most of the students did not comprehend the formula and the concept of present perfect tense. Then, they were less practice at home and they did not focus while studying. This topic was also less interesting to the students and they were still lacked of the vocabularies to produce the sentence with the right form of present perfect tense. Thus, it can be concluded it is difficult for the students to use the present perfect tense in a communicative test.